2012
DOI: 10.1017/s001708951200002x
|View full text |Cite
|
Sign up to set email alerts
|

On Stable Quadratic Polynomials

Abstract: Abstract. We recall that a polynomial f (X) ∈ K[X] over a field K is called stable if all its iterates are irreducible over K. We show that almost all monic quadratic polynomials f (X) ∈ ‫[ޚ‬X] are stable over ‫.ޑ‬ We also show that the presence of squares in so-called critical orbits of a quadratic polynomial f (X) ∈ ‫[ޚ‬X] can be detected by a finite algorithm; this property is closely related to the stability of f (X). We also prove there are no stable quadratic polynomials over finite fields of characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…In this paper we specialize on irreducibility questions regarding compositional semigroups of polynomials. This kind of question has been addressed in the specific case of semigroups generated by a single quadratic polynomial, see for example in [6,5,11,10], for analogous results related to additive polynomials, see [14,15]. It is worth mentioning that one of these results [11,Lemma 2.5] has been recently used in [16] by the first and the second author of the present paper to prove [12,Conjecture 1.2].…”
Section: Introductionmentioning
confidence: 84%
“…In this paper we specialize on irreducibility questions regarding compositional semigroups of polynomials. This kind of question has been addressed in the specific case of semigroups generated by a single quadratic polynomial, see for example in [6,5,11,10], for analogous results related to additive polynomials, see [14,15]. It is worth mentioning that one of these results [11,Lemma 2.5] has been recently used in [16] by the first and the second author of the present paper to prove [12,Conjecture 1.2].…”
Section: Introductionmentioning
confidence: 84%
“…Figure 2. This shows that the irreducible compositions of f and g are precisely those of the form f (n) , f (n) • g, f (n) • g (2) and f (n) • g (2) • f for n ≥ 0.…”
Section: 3mentioning
confidence: 90%
“…Applying the construction, we get the automaton shown in Figure 3. We see that the irreducible polynomials in C S are exactly x, h, h • g • f (n) for n ≥ 0, and h (2) • k for k ∈ C S arbitrary (possibly the identity). Applying Theorem 3.11, it follows that the set of irreducible polynomials in F 3 [x] that can be written as a nonempty composition of degree 2 polynomials is precisely…”
Section: 3mentioning
confidence: 97%
See 1 more Smart Citation
“…We also noted in the introduction that Odoni [11] studied the stability of additive polynomial f (x) = x p − x − 1 over F p . His method is different from the methods of the current paper and those of [1,7]. Using Capelli's lemma he showed that the Galois group of f f (x) over F p is the cyclic group of order p and hence f f (x) is not stable.…”
Section: Discussionmentioning
confidence: 75%